O caso da escola municipal Campos Salles (Heliópolis-SP) e a construção da autonomia - Hora, Carolina Laureto (Universidade Federal de São Carlos, 2019)
The discussions in Dialetics of enligghtenmentby Adorno and Horkheimer and in the Theory of Semi-formation by Adorno, denounce that the cultural formation prevailing in capitalist society is based on technical rationality that leads men back to barbarism and defend an education that can emancipate the subjects instead of rendering their critical reflection unfeasible. Starting from the conception of emancipation developed by critical theorists as a theoretical strategy and based on a bibliographical survey about transformations proposed by new educational models, this research aims to identify, understand and analyze how the emancipatory ethos materializes in a school institution of the city of São Paulo, EMEF Presidente Campos Salles, which has a special pedagogical political project based on the model of a Portuguese democratic school, Escola da Ponte. Thus, an empirical study was developed in that institution that focused mainly on the established relationship between teachers and students, taken in the present work as a crucial element for the construction of the autonomy, in agreement with the studies of Paulo Freire. The methodology used for the data collection consisted of qualitative field research in which interviews were conducted with students and teachers, and the methodology of analysis used was the Objective Hermeneutics, through which the transcripts of the interviews were submitted to a collective analysis of members of the Critical Theory and Education Research Group, headquartered at the Department of Education of UFSCar - Ded / UFSCar. The conclusions of the present work, based on the case study of the school from São Paulo, point to a significant development of the autonomy of the interviewed subjects as a process, and not as something ready or determined by the institution itself. The present study seeks to contribute to studies in the area of Critical Theory in Brazil by promoting a critical analysis of innovative educational proposal in progress in the country.
The case of the Campos Salles municipal school (Heliópolis-SP) and the construction of autonomy
Keywords: Teoria crítica; Autonomia; Inovação educacional; Escolas democráticas; Hermenêutica objetiva; Critical theory; Autonomy; Educational innovation; Democratic schools; Objective hermeneutics; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO